INTIMA-MEDIA THICKNESS OF THE CAROTID ARTERIES IS AFFECTED BY PUBERTAL MATURATION IN HEALTHY ADOLESCENTS - Zanini,Jovita Lane Soares Santos (2019)
ABSTRACT Objective: To contribute to the assessment of normal parameters of carotid intima-media thickness (CIMT) in healthy adolescents. Methods: A cross-sectional study was conducted through clinical, laboratory and ultrasound evaluation in 61 healthy adolescents. The inclusion criteria consisted of being in good health. The exclusion criteria were: presence or history of any chronic disease; being obese or overweight according to the World Health Organization (WHO) established criterion; continuous use of medication; or presenting a febrile condition or requiring medication within 48-hours prior to assessment. The pubertal stages were evaluated using the Tanner criteria. The high-resolution B-mode ultrasound examinations were performed according to the recommendations of the Consensus Statement from the American Society of Echocardiography Carotid Intima-Media Thickness Task Force. Results: Adolescents were 14±2.6 years old, 62.3% female, 19 (31%) at early puberty (Tanner II and III), and 38 (62%) at late puberty (Tanner IV and V). They presented normal clinical and laboratorial parameters. CIMT values were 0.46±0.04 to 0.55±0.04 mm on the right and 0.48±0.02 to 0.53±0.04 mm on the left, according to pubertal maturation. CIMT values increased significantly on the right and left sides, according to pubertal stage (p<0.001 and p=0.016), and maximum internal diameters of the common carotid artery (p<0.025 and p<0.003). It was higher in males compared to females. Conclusions: An increase in CIMT in the healthy adolescents group, according to both age, and the degree of pubertal maturation should be considered when evaluating adolescents in diagnostic procedures.